Piezo-phototronic effect enhanced self-powered and broadband photodetectors based on Si/ZnO/CdO three-component heterojunctions. (October 2017) - Yin, Bing; Zhang, Heqiu; Qiu, Yu; Luo, Yingmin; Zhao, Yu; Hu, Lizhong
Abstract: The broadband and self-powered photodetectors have attracted significant attention due to the versatility and without extra energy. In this work, we fabricate a self-powered and broadband photodetector based on Si/ZnO/CdO three-component heterojunctions. The photodetector has a fast response time (shorter than 0.45 s) to the ultraviolet and visible illumination at 0 V bias. CdO film is used as the transparent electrode because of the superior electrical characterization and the appropriate band structure of ZnO/CdO, which facilitates electrons transferring from ZnO nanorods to the CdO electrode and reflects holes back into the ZnO, thus reducing recombination at the ZnO/CdO interface and enhancing photocurrent. Moreover the performance of the photodetector is optimized and significantly enhanced by the piezo-phototronic effect of ZnO nanorods. This work may provide a potential approach to enhance the performance of self-powered and broadband photodetectors. Graphical abstract: Piezo-phototronic effect enhances photodetectors based on Si/ZnO/CdO three-component heterojunctions. Highlights: A broadband photodetector based on Si/ZnO/CdO heterojunctions is fabricated. Thepotential barrierat ZnO/CdO interface reduces the possibility of recombination. The piezo-phototronic effect is used to enhance the performance of photodetectors.